Religion in Childhood and Adolescence: How should it be studied?: A Critical Review of Problems and Challenges in Methodology and Research - Schweitzer, Friedrich (Journal of empirical theology, 2014)
This article discusses the question of how religion in childhood and adolescence should be studied. More exactly, the focus is on problems of methodology and research which are discussed in relationship to religion in childhood and adolescence. It does not present a handbook type of overview, however, but is focused on problems and challenges for future research. Four questions are addressed specifically: How can empirical research do justice to the special nature of religion in childhood and adolescence? What are the implications of viewing religion within non-religious interpretive frameworks? What methodological problems do we have to face concerning religion in childhood and adolescence? What interdisciplinary challenges can be identified in this context? The final section relates these questions to the main topic of the present publication by stating a number or criteria, i.e., criteria related to the concept of religion to be used in research across different approaches and disciplines.